Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/jee/tow210
|View full text |Cite
|
Sign up to set email alerts
|

Residual and Systemic Efficacy of Chlorantraniliprole and Flubendiamide Against Corn Earworm (Lepidoptera: Noctuidae) in Soybean

Abstract: Experiments were conducted in Mississippi from 2013 to 2015 to determine the systemic and residual efficacy of chlorantraniliprole and flubendiamide against corn earworm, Helicoverpa zea (Boddie), in soybean. Both insecticides were applied at V4 and R3. Ten leaves that were present at the time of application and 10 newly emerged leaves that were not present at the time of application were collected to measure residual and systemic efficacy, respectively. Ten pods were removed from each plot at R5.5. For all as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
3
24
0
1
Order By: Relevance
“…Chlorantraniliprole proved to be absorbed and translocated upward in soybean plants only when applied to stems or sprayed throughout the plant [7]. This application in the leaves and petioles did not result in the mortality of larvae feeding on new leaves, confirming the hypothesis that chlorantraniliprole is translocated only via xylem [7]. However, our results showed that chlorantraniliprole and cyantraniliprole, when applied in foliar spraying, were not translocated from treated to new untreated leaves of corn plants.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Chlorantraniliprole proved to be absorbed and translocated upward in soybean plants only when applied to stems or sprayed throughout the plant [7]. This application in the leaves and petioles did not result in the mortality of larvae feeding on new leaves, confirming the hypothesis that chlorantraniliprole is translocated only via xylem [7]. However, our results showed that chlorantraniliprole and cyantraniliprole, when applied in foliar spraying, were not translocated from treated to new untreated leaves of corn plants.…”
Section: Discussionsupporting
confidence: 76%
“…Insecticides applied by foliar spraying were not detected on all leaves evaluated after spraying, meaning that the active ingredients are not mobile via phloem. Chlorantraniliprole proved to be absorbed and translocated upward in soybean plants only when applied to stems or sprayed throughout the plant [7]. This application in the leaves and petioles did not result in the mortality of larvae feeding on new leaves, confirming the hypothesis that chlorantraniliprole is translocated only via xylem [7].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…A series of experiments conducted during 2017 in North Carolina demonstrated the potential for the revival of an egg‐based threshold for bollworm in two‐Bt‐toxin cotton using the insecticide chlorantraniliprole. This technique was pioneered in the Midsouth and took advantage of the fact that this insecticide was xylem mobile (Lahm et al, 2007), translaminar, could move to newly grown vegetative tissue after application, and provided relatively extended residual (Adams et al, 2016b). The North Carolina experiments were initiated using foliar chlorantraniliprole (Prevathon) applications when bollworm eggs were deposited in Bt cotton, but larvae were not present, and when bollworm eggs were present, along with some larvae, in non‐Bt cotton (despite Cry resistance, larvae still developed more slowly on Bt cotton during 2017).…”
Section: Revival Of An Egg‐based Threshold?mentioning
confidence: 99%
“…In soybean, bollworm can currently be controlled using foliar insecticides. For example, a recent survey of bollworm populations across the southern U.S. found that they were very susceptible to diamide‐class insecticides (Adams et al, 2016a) and that these could be effective, if used properly, in soybean (Adams et al, 2016b). While pyrethroid‐resistant bollworm populations have been present since the 1990s, use of this class for bollworm in both cotton and soybeans was still widespread until the 2010s.…”
mentioning
confidence: 99%